Evaluation of Lactobacillus brevis MG000874 in Behavioral and In Vitro Antioxidant Enzyme Activity of Murine Brain - Saleha Noureen; Iram Liaqat; Ayesha Riaz; Mehwish Rana; Najma Arshad (Brazilian Archives of Biology and Technology, 2022)
Abstract Aging and oxidative stress are important biological processes with extensive medical and social significance. The D-Galactose (D-Gal) has been used in animals for inducing oxidative stress and brain aging. The present study was conducted to evaluate the role of Lactobacillus brevis MG000874 in inhibiting the aging process and oxidative stress in D-Gal induced oxidative stress murine model. The cognitive responses and biochemical indicators were used to estimate the anti-aging and antioxidant potential of L. brevis MG000874 in mice. Tests used to assess cognitive responses, included object recognition, open field and T Maze. While antioxidant status was assessed by measuring superoxide dismutase (SOD), catalase (CAT), glutathione (GSH) and glutathione-S-transferase (GST) activity in mice brain tissues. Results suggested that D-Gal can seriously impair the object recognition in mice. It led to significant reduction in ambulation, rearing, leaning and grooming. Similar trend was observed in antioxidant enzymes such as SOD, CAT and GSH except for GST where elevation was observed. Treatment with L. brevis MG000874 and ascorbic acid inhibited this reduction and kept levels close to control. Likewise, values of GSH of probiotic group were lower than negative control but significantly higher than positive control group. Probiotic supplementation in the presence of D-Gal displayed improvement in GSH, while no such improvement could be observed with ascorbic acid treatment. It can be concluded from the present study that L. brevis MG000874 can be used as anti-aging and antioxidant agent. It is recommended that L. brevis MG000874 could be included in the list of probiotics.